Experimental study on the rheological behavior of silver-heat transfer oil nanofluid and suggesting two empirical based correlations for thermal conductivity and viscosity of oil based nanofluids. (25th May 2016) - Aberoumand, Sadegh; Jafarimoghaddam, Amin; Moravej, Mojtaba; Aberoumand, Hossein; Javaherdeh, Kourosh
Highlights: Measuring thermal conductivity and viscosity of three fractions of nanofluids. Introducing an empirical based correlation for thermal conductivity. Introducing an empirical based correlation for viscosity of oil based nanofluids. A novel one-step method for preparation nanofluids has been discussed in brief. Graphical Abstract: Abstract: Thermal conductivity and viscosity of nanofluids are the most important parameters that have to be determined specially, for industrial applications. Therefore, it is beneficial to precisely predict the thermal conductivity and viscosity of nanofluids. Because of the fact that experimental instruments are not possible in many situations, and present models are not applicable for any nanofluids, new correlations have been developed based on the data of oil based nanofluids in the literature. The proposed correlations are based on the bulk temperature, nanoparticle diameter and nanoparticle concentration as input variables. Since the published data studying rheological properties of oil based nanofluids were not found to be in a huge database, thermal conductivity and viscosity of heat transfer oil were investigated experimentally to be added to our database. The results showed that previous models for thermal conductivity of nanofluids predict thermal conductivity of oil based nanofluids in a decreasing way versus baulk temperature while, thermal conductivity of oil based nanofluids increases with rising temperature. So, this could be the motivation to develop an accurate correlation for thermal conductivity, specialized for oil based nanofluids. On the other hand, a new correlation for predicting viscosity of oil based nanofluids has been introduced. According to the results, the accuracy of the proposed correlation is in a better situation than other popular models.